A hot spot analysis on nursing research of cerebrovascular angiography in China - ZHANG, Yanyan; LIU, Guiying; GUO, Hong (Chinese Journal of Integrative Nursing, 2021)
Objective To systematically sort out the research literature on cerebrovascular angiography nursing in my country, to discuss the research status, hot spots and development trends of cerebrovascular angiography nursing, and to provide references for clinical staff engaged in cerebrovascular angiography nursing in China. Methods Taking the nursing of cerebral angiography as the subject, searching domestic common databases including CNKI, VIP, Wanfang, and using CiteSpace software to visually analyze the retrieved documents. Results A total of 1088 articles were included, combined with keyword co-occurrence and burstiness, etc. , it was concluded that the research in the field of cerebral angiography in my country mainly focuses on the effectiveness of different nursing methods and new nursing techniques in reducing perioperative complications. Conclusion Based on evidence-based, graded assessment of the risk factors that cause urinary retention after cerebrovascular angiography and individualized response measures based on different risk grading standards, continuous optimization of nursing intervention methods, and increased patient comfort are the future Research trends. (目的 系统梳理我国有关脑血管造影术护理的研究文献, 探讨脑血管造影术护理的研究现状、热点及发展趋势, 为我国从事脑血管造影术护理的临床工作人员提供参考。方法 以脑血管造影术护理为主题, 检索国内常用数据库包括中国知网、维普、万方, 运用CiteSpace软件对检索到的文献进行可视化分析。结果 共纳入1088篇文献, 结合关键词共现及突现词等, 得出我国脑血管造影术护理领域的研究主要围绕不同的护理方式以及护理新技术等对减少围手术期并发症有效性方面展开。结论 以循证为基础, 对引起脑血管造影术后尿潴留的危险因素进行分级评估, 针对不同的风险分级标准开展个性化的应对措施, 不断优化护理干预方式, 增加患者舒适性等是未来研究的趋势。)